Logics of career choice - concept and results of an approval-sensitive career guidance workshop - Mutlu, Sevil; Ziegler, Birgit; Granato, Mona (Frontiers in Psychology, 2024)
To manage the transition from school to work, young people need to learn about occupations, explore their own (professional) interests, skills and values, and make career-related decisions. According to Gottfredson’s Career Construction (CC) theory (1981), young people - influenced by their need for social approval - have already narrowed down their spectrum of acceptable occupations by the time they participate in school-based career orientation programs. Therefore, we focus on career guidance interventions that take into account their need for social approval. We present first results of an intervention study of a newly developed approval-sensitive workshop, “Logic of Career Choice.” It challenges students’ mostly unconscious need for social approval, raising awareness and prompting reflection and action on this aspect of their career choices. By analyzing a sample based on a quasi-experimental treatment-control group research design, we examine to what extent this workshop can contribute to reaching its objectives [n = 1236 students in secondary schools; treatment group (n = 766); control group (n = 470)]. Confirmatory factor analyses indicate the reliability of the new measurement instruments. The six examined constructs include (1) the relevance of social approval, (2) the feeling of autonomy, (3) interest in career choice, (4) reflection of needs, (5) intention to act, and (6) reported career choice activities. The results reveal partial confirmation of hypothesis (1) regarding the importance of social approval and (2) the feeling of autonomy. However, the constructs (4) reflection of needs and (5) intention to act show parallel developments in both the treatment and control groups, leading to the rejection of these hypotheses. The constructs (3) interest in career choice and (6) retrospectively reported activities regarding career choice show unexpected effects of the workshop. Interest in career choice decreases significantly more in the treatment group than in the control group, and the treatment group reports significantly more retrospective career choice activities. The discussion interprets the results in the context of their scientific and practical implications, with special attention given to the decrease in interest in career choice in the treatment group and the increased retrospective reporting of career choice activities.